2000
DOI: 10.1073/pnas.97.12.6322
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer discrimination illustrated by high-resolution crystal structures of the human nuclear receptor hRARγ

Abstract: The human retinoic acid receptor (hRAR) is a member of the nuclear receptor superfamily that regulates the transcription of target genes in a ligand-dependent manner. The three hRAR isotypes are targets for retinoids that are used in the treatment of various diseases, including breast cancer and skin diseases. Drug efficiency and safety depend on the pharmacological activity of enantiomers, which can differ because of the chiral environment generated by the target. We report the crystal structures of the hRAR␥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 27 publications
3
66
0
Order By: Relevance
“…The protein structures are identical to that observed in the complex with the natural ligand. A similar observation has already been made for retinoic acid receptor, where numerous complexes with the two natural ligands (all-trans-and 9-cis-retinoic acid) and synthetic analogs revealed that the ligand-binding pocket was unchanged and that it is the ligand that adapts (26)(27)(28)(29). Such observations should be valid not only for retinoic acid receptor and VDR but most likely also for other NRs.…”
Section: Discussionmentioning
confidence: 55%
“…The protein structures are identical to that observed in the complex with the natural ligand. A similar observation has already been made for retinoic acid receptor, where numerous complexes with the two natural ligands (all-trans-and 9-cis-retinoic acid) and synthetic analogs revealed that the ligand-binding pocket was unchanged and that it is the ligand that adapts (26)(27)(28)(29). Such observations should be valid not only for retinoic acid receptor and VDR but most likely also for other NRs.…”
Section: Discussionmentioning
confidence: 55%
“…26−30 Numerous modifications of the basic scaffold have been systematically carried out in order to correlate structure and functional consequences of retinoid ligand modifications on receptor activation. 17−19 Substitution at the naphthalene C8 position afford in general ligands with RAR antagonist/inverse agonist activities, 28−30 and this is modulated 31 by synergy with halogen atoms at the C3 position 32 of the benzoic acid terminus. In these structures, the LBP volume around the naphthalene C5 position is filled with a hydrophobic gemdimethyl group.…”
mentioning
confidence: 99%
“…Ligand 11a was positioned in the active site on the basis of the canonical positions revealed by the crystal structures. [20][21][22]32,43,44 Preferred docking sites for functional groups were evaluated with the program GRID, 45 which assisted in the selection of binding modes. 31 The resulting model showed the two phenyl moieties at C5 and C8 positions running almost perpendicular to the ethenylbenzoic acid buried in a predominantly hydrophobic pocket (Figure 4).…”
mentioning
confidence: 99%
“…Energy-minimized conformers of AHPN [1], RAR-selective trans-RA [3], and RAR-selective TTAB [5] (39) were overlapped. The trans-RA conformer was that reported in the RARy LBD (40,41). Three orthogonal views of these overlaps are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%